Pandora's Box Ethnography and the Comparison of Medical Beliefs - Lewis, Gilbert (HAU Books, 2021)
In this book, written between 1979 and 2020, Gilbert Lewis distills a lifetime of insights he garnered as a medical anthropologist. He asks: How do beliefs about illness in different societies influence their members' ability to heal? Despite the advances of Western medicine, what can it learn from non-Western societies that consider sickness and curing to be as much a matter of social relationships as biological states? What problems arise when one set of therapeutic practices displaces another?Lewis compares Indigenous medical beliefs in New Guinea in 1968, when villagers were largely self-reliant, and in 1983, after they became dependent on Western medicine. He then widens his comparative scope by turning to West Africa and discussing a therapeutic community run by a prophet who heals the ill through confession and long-term residential care.Pandora's Box began life with the prestigious Lewis Henry Morgan Lectures that Gilbert Lewis delivered in 1979 at the University of Rochester. He expanded them with materials gathered over the next forty years, completing the manuscript a few weeks before his death. Engagingly written, this book will inspire anthropologists, medical professionals, students, and curious readers to look with new eyes at current crises in world health.